Division of monomials means product of their quotient of numerical coefficients and quotient of their literal coefficients.

Since, the product of 3m and 5n = 3m × 5n = 15mn; it follows that

(i) \(\frac{15mn}{3m} = \frac{3 \times 5 \times m \times n}{3 \times m}\) = 5n

or, 15mn ÷ 3m = 5n

i.e. when 15mn is divided by 3m, the quotient is 5n.

(ii) \(\frac{15mn}{5n} = \frac{3 \times 5 \times m \times n}{5 \times n}\) = 3m

or, 15mn ÷ 5n = 3m

i.e. when 15mn is divided by 5n, the quotient is 3m.

**1.** Divide 35mxy
by 5my

35mxy ÷ 5my

= \(\frac{35mxy}{5my}\)

Now, we need to write each term in the expanded form and then cancel the terms which are common to both numerator and denominator.

= \(\frac{\not{5} \times 7 \times \not{m} \times x \times \not{y}}{\not{5} \times \not{m} \times \not{y}}\)

= 7x

14a

= \(\frac{14a^{7}}{2a^{5}}\)

Now, we need to write each term in the expanded form and then cancel the terms which are common to both numerator and denominator.

= \(\frac{\not{2} \times 7 \times \not{a} \times \not{a} \times \not{a} \times \not{a} \times \not{a} \times a \times a}{\not{2} \times \not{a} \times \not{a} \times \not{a} \times \not{a} \times \not{a}}\)

= 7 × a × a= 7a

14a

= \(\frac{14a^{7}}{2a^{5}}\)

= \(\frac{14}{2} \times \frac{a^{7}}{a^{5}}\)

Now we will write the each numerical part \((\frac{14}{2})\) in the expanded form and then cancel the terms which are common to both numerator and denominator and in case of literal part subtract the smaller power of a literal from bigger power of the same literal.

= \(\frac{\not{2} \times 7}{\not{2}} \times a^{7 - 5}\)

= 7 ×= 7a

81p

= \(\frac{81p^{3}q^{6}}{27p^{6}q^{3}}\)

= \(\frac{81}{27} \times \frac{p^{3}q^{6}}{p^{6}q^{3}}\)

Now we will write the each numerical part (\frac{81}{27}) in the expanded form and then cancel the terms which are common to both numerator and denominator and in case of literal part subtract the smaller power of a literal from bigger power of the same literal.

= \(\frac{\not{3} \times \not{3} \times \not{3} \times 3}{\not{3} \times \not{3} \times \not{3}} \times \frac{q^{6 - 3}}{p^{6 - 3}}\)

= \(3 \times \frac{q^{3}}{p^{3}}\)

= \(\frac{3q^{3}}{p^{3}}\)

**● ****Terms of an Algebraic Expression**

Types of Algebraic Expressions

Multiplication of Two Monomials

Multiplication of Polynomial by Monomial

Multiplication of two Binomials

__Algebra Page____6th Grade Page____From Division of Monomials to HOME PAGE__

**Didn't find what you were looking for? Or want to know more information
about Math Only Math.
Use this Google Search to find what you need.**

**● ****Terms of an Algebraic Expression - Worksheet**

Worksheet on Types of Algebraic Expressions

Worksheet on Degree of a Polynomial

Worksheet on Addition of Polynomials

Worksheet on Subtraction of Polynomials

Worksheet on Addition and Subtraction of Polynomials

Worksheet on Adding and Subtracting Polynomials

Worksheet on Multiplying Monomials

Worksheet on Multiplying Monomial and Binomial

Worksheet on Multiplying Monomial and Polynomial

## New! Comments

Have your say about what you just read! Leave me a comment in the box below. Ask a Question or Answer a Question.